Mental stress grading based on fNIRS signals - Al-Shargie, F. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this study, we propose functional near infrared spectroscopy (fNIRS) to objectively grade different levels of mental stress. The levels of stress were set based on the difficulty of arithmetic task, time pressure and negative feedback about peer performance. We examined the proposed approach on twelve human subjects using the Montreal Imaging Stress Task. The experiment results revealed a reduction in cortical activation at prefrontal cortex when stressed, and the differences in hemodynamic response between control condition and under stress were significant for arithmetic difficulty level one, two and three, respectively, (p = 0.0023, 0.0001 and 0.0004). The experiment results thus support the suggestion of fNIRS in grading mental stress. Â© 2016 IEEE.